## RS Aggarwal Class 7 Solutions Chapter 6 Algebraic Expressions Ex 6C

These Solutions are part of RS Aggarwal Solutions Class 7. Here we have given RS Aggarwal Solutions Class 7 Chapter 6 Algebraic Expressions Ex 6C.

**Other Exercises**

- RS Aggarwal Solutions Class 7 Chapter 6 Algebraic Expressions Ex 6A
- RS Aggarwal Solutions Class 7 Chapter 6 Algebraic Expressions Ex 6B
- RS Aggarwal Solutions Class 7 Chapter 6 Algebraic Expressions Ex 6C
- RS Aggarwal Solutions Class 7 Chapter 6 Algebraic Expressions Ex 6D

**Find each of the following products:**

**Question 1.**

**Solution:**

4a(3a + 7b) = 4a x 3a + 4a x 7b = 12a^{2} + 28ab

**Question 2.**

**Solution:**

5a(6a – 3b) = 5a x 6a – 5a x 3b = 30a^{2} – 15ab

**Question 3.**

**Solution:**

8a^{2 }(2a + 5b) = 8a^{2} x 2a + 8a^{2} x 5b = 16a^{3} + 40a^{2}b

**Question 4.**

**Solution:**

9x^{2} (5x + 7) = 9x^{2} x 5x + 9x^{2} x 7 = 45x^{3} + 63x^{2}

**Question 5.**

**Solution:**

ab(a^{2} – b^{2}) = ab x a^{2} – ab x b^{2} = a^{3}b – ab^{3}

**Question 6.**

**Solution:**

2x^{2} (3x – 4x^{2}) = 2x^{2} x 3x – 2x^{2} x 4x^{2} = 6x^{3} – 8x^{4}

**Question 7.**

**Solution:**

**Question 8.**

**Solution:**

-1 7x^{2} (3x – 4) = -17x^{2} x 3x – 17x^{2} x (-4) = -51x^{3} + 68x^{2}

**Question 9.**

**Solution:**

**Question 10.**

**Solution:**

-4x^{2}y (3x^{2} – 5y)

= -4x^{2 }y x 3x^{2} – 4x^{2 }y x (-5y)

= -12x^{2 }y + 20x^{2 }y^{2}

**Question 11.**

**Solution:**

**Question 12.**

**Solution:**

9t^{2} (t + 7t^{3}) = 9t^{2} x t + 9t^{2} x 7t^{3} = 9t^{3} + 63t^{5}

**Question 13.**

**Solution:**

**Question 14.**

**Solution:**

**Question 15.**

**Solution:**

**Question 16.**

**Solution:**

24x^{2} (1 – 2x)

= 24x^{2} x 1 – 24x^{2} x 2x

= 24x^{2} – 48x^{3}

If x = 2, then

24x^{2} – 48x^{3}

= 24(2)^{2} – 48(2)^{3}

= 24 x 4 – 48 x 8

= 96 – 384

= -288

**Question 17.**

**Solution:**

**Question 18.**

**Solution:**

s (s^{2} – st) = s x s^{2} – s x st = s^{3} – s^{2}t

If s = 2, t = 3, then

s^{3} – s^{2}t = (2)^{3} – (2)^{2} x 3 = 8 – 4 x 3 = 8 – 12 = -4

**Question 19.**

**Solution:**

-3y (xy + y^{2}) = -3y x xy + (-3y) x y^{2} = -3xy^{2} – 3y^{3}

if x = 4, y = 5, then

-3xy^{2} – 3y^{3}

= -3(4)(5)^{2} – 3(5)^{3} = -3 x 4 x 25 – 3 x 125 = -300 – 375 = -675

**Simplify each of the following:**

**Question 20.**

**Solution:**

a(b – c) + b(c – a) + c(a – b) = ab – ac + bc – ab + ac – bc = 0

**Question 21.**

**Solution:**

a(b – c) – b(c – a) – c(a – b) = ab – ac – bc + ab – ac + bc = 2ab – 2ac

**Question 22.**

**Solution:**

3x^{2} + 2(x + 2) – 3x (2x + 1)

= 3x^{2} + 2x + 4 – 6x^{2} – 3x = 3x^{2} – 6x^{2} + 2x – 3x + 4 = -3x^{2} – x + 4

**Question 23.**

**Solution:**

x (x + 4) + 3x (2x^{2} – 1) + 4x^{2} + 4

= x^{2} + 4x + 6x^{3} – 3x + 4x^{2} + 4

= 6x^{3} + x^{2} + 4x^{2} + 4x – 3x + 4

= 6x^{3} + 5x^{2} + x + 4

**Question 24.**

**Solution:**

2x^{2} + 3x (1 – 2x^{3}) + x (x + 1)

= 2x^{2} + 3x – 6x^{4} + x^{2} + x

= – 6x^{4} + 2x^{2} + x^{2} + 3x + x

= – 6x^{4} + 3x^{2} + 4x

**Question 25.**

**Solution:**

a^{2}b (a – b^{2}) + ab(4ab – 2a^{2}) – a^{3}b (1 – 2b)

= a^{3}b – a^{2}b^{3} – 2a^{3}b^{2} + 4a^{2}b^{3} – 2a^{3}b^{2} – a^{3}b + 2a^{3}b^{2}

= a^{3}b – a^{3}b + 2a^{3}b^{2} – a^{2}b^{3} + 4a^{2}6^{3}

= 3a^{2}b^{3}

**Question 26.**

**Solution:**

4st (s – t) – 6s^{2} (t – t^{2}) – 3t^{2} (2s^{2} – s) + 2st(s – t)

= 4s^{2}t – 4st^{2} – 6s^{2}t + 6s^{2}t^{2} – 6s^{2}t^{2} + 3st^{2} + 2s^{2}t – 2st^{2}

= 4s^{2}t – 6s^{2}t + 2s^{2}t – 4st^{2} + 3st^{2} – 2st^{2} + 6s^{2}t^{2} – 6s^{2}t^{2}

= 6s^{2}t – 6s^{2}t – 6st^{2} + 3st^{2} + 6s^{2}t^{2} – 6s^{2}t^{2}

= – 3st^{2}

Hope given RS Aggarwal Solutions Class 7 Chapter 6 Algebraic Expressions Ex 6C are helpful to complete your math homework.

If you have any doubts, please comment below. Learn Insta try to provide online math tutoring for you.